Triggering Bimodal Radial Stem Growth in Pinus sylvestris at a Drought-Prone Site by Manipulating Stem Carbon Availability - Oberhuber, Walter; Landlinger-Weilbold, Anton; Schröter, Dennis Marko (Frontiers in Plant Science, 2021)
A bimodal radial growth (RG) pattern, i.e. growth peaks in spring and autumn, was repeatedly found in trees in Mediterranean regions, where summer drought causes reduction or cessation of cambial activity. In a dry inner Alpine valley of the Eastern Alps (Tyrol, Austria, 750 m asl) Pinus sylvestris shows unimodal RG with onset and cessation of cambial activity in early April and late June, respectively. A resumption of cambial activity after intense summer rainfall was not observed in this region. In a field experiment we tested the hypothesis that early cessation of cambial activity at this drought-prone site is an adaptation to limited water availability leading to an early and irreversible switch of carbon (C) allocation to belowground. To accomplish this, the C status of young Pinus sylvestris trees was manipulated by physical blockage of phloem transport (girdling) six weeks after cessation of cambial cell division. Influence of manipulated C availability on RG was recorded by stem dendrometers, which were mounted above the girdling zone. In response to blockage of phloem flow, resumption of cambial activity was detected above girdling after about two weeks. Although the experimentally induced second growth surge lasted for the same period as in spring (c. two months), the increment was more than twice as large due to doubling of daily maximum RG rate. After girdling wood anatomical traits above girdling no longer showed any significant differences between earlywood and latewood tracheids indicating pronounced effects of C availability on cell differentiation. Below girdling no reactivation of cambial activity occurred, but cell wall thickness of last formed latewood cell was reduced due to lack of C supply after girdling. Intense RG resumption in Pinus sylvestris after girdling indicates that cessation of cambial activity can be reversed by manipulating C status of the stem. Hence, our girdling study yielded strong support for the hypothesis that belowground organs exert high C sink strengths on the drought-prone study site. Furthermore, this work highlights the need of in-depth experimental studies in order to understand the interactions between endogenous and exogenous factors on cambial activity and xylem cell differentiation more clearly.